Antimicrobial activity and resistance selection of different bioglass S53P4 formulations against multidrug resistant strains. (August 2015) - Drago, Lorenzo; Vecchi, Elena De; Bortolin, Monica; Toscano, Marco; Mattina, Roberto; Romanò, Carlo Luca
Aims : This study aimed to evaluate the antimicrobial activity of two different formulations of bioglass BAG-S53P4 against multiresistant microorganisms involved in bone infections, and the capability of bioglass to select for resistance.Methods: Antibacterial activity was evaluated by means of killing curves. The ability to select for resistant bacteria was evaluated by subculturing microorganisms in serial dilutions of bioglass. Scanning electron microscope acquisitions were conducted to evaluate bioglass-induced morphology changes.Results: BAG-S53P4 formulations display a high antimicrobial activity and do not seem to select for resistance. Scanning electron microscopy analysis showed cell shrinkage and membrane damage after exposure to bioglass.Conclusions: BAG-S53P4 has a significant potential as bone substitute for the treatment of infections caused by multiresistant microorganisms.